Banksy in commercial communication: Street Art and appropriationism - López, Matías; Martín-Ortega, Lara; Bellido-Blanco, Santiago (Street Art & Urban Creativity, 2022)
The advertising market draws on elements and aesthetics from other areas and disciplines, appropriating artistic imaginaries of Street Art, subverting them to change the user's perception of messages. The media increasingly show creative solutions that take ideas from the art world as a reference. They reuse pre-existing images to give them a new message that responds to a different discourse. In this article, we will study how the imaginary of advertising appropriates urban movements, analysing the influences of the artist Banksy on persuasive commercial activity and vice versa. The conclusions of this analysis are that the very appropriation, an inherent consequence of the art and advertising binomial, improves the creative dimension of the works in both areas. Communication tends to reuse the artistic imaginary for commercial purposes, while the artist drinks from commercial aesthetics to represent the reality in which he lives. There is also a proliferation of the number of pieces related to the actions of the author Banksy in recent years. Observing iconography and techniques of persuasive communication in the work of this anonymous author.